Wideo o ukraińskiej góralce karpackiej jako przykład efektywności komunikowania w serwisie YouTube - Dudziak, Arkadiusz (Przegląd Wschodnioeuropejski, 2025)
The article was inspired by the popularity on YouTube of a Ukrainian woman, Maria Dmitroniak, a resident of the Carpathian village of Dzembronia. One of the videos about this woman’s everyday life and cooking has received over 14.5 million views since 2022. The Food Around The World channel has become an example of the effectiveness of audiovisual communication on YouTube. The film about the Ukrainian highlander took on the characteristics of an axiological message. The article describes the online reception of the film. The most representative comments of YouTube users were subjected to axiological analysis. The reception of this video on YouTube creates an axiosphere in which not only aesthetic, but also ethical and even religious values are manifested.